Prevalensi Parasit Soil Transmitted Helminths Pada Anak Usia 2-9 Tahun Di Rukun Warga 04 Kelurahan Batakte Kecamatan Kupang Barat Kabupaten Kupang Tahun 2017 - Ni Made Susilawati; Rini Kurniaty Smaut (JURNAL INFO KESEHATAN, 2017)
Infection worm is one of the many diseases that occur in the community but less attention. This can be due to the worm group Soil-Transmitted Helminths (STH), a group of worms that cycle through the soil life, namely Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis, Necator americanus and Ancylostoma sp. Children more often found STH infected. The purpose of this study is to determine the prevalence of STH parasites in children aged 2-9 years in RW 04 Batakte Urban Village, Kupang Barat District, Kupang District in 2017. This type of research is a descriptive research that is the prevalence of Soil-Transmitted Helminths parasite. The subjects of this study were 59 children collected by total sampling method. The feces of the study subjects were collected, then examined by the native method to determine STH infection. The result of the research that has been done, the prevalence of Soil-Transmitted Helminths parasite in children aged 2-9 years in RW 04 Batakte urban village is 12% is 7 samples positive Ascaris lumbricoides (Ascariasis).